Modes and mechanisms for the inheritance of mitochondria and plastids in pathogenic protists. - Sophie L Collier; Sarah N Farrell; Christopher D Goodman; Geoffrey I McFadden (PLoS Pathogens)
Pathogenic protists are responsible for many diseases that significantly impact human and animal health across the globe. Almost all protists possess mitochondria or mitochondrion-related organelles, and many contain plastids. These endosymbiotic organelles are crucial to survival and provide well-validated and widely utilised drug targets in parasitic protists such as Plasmodium and Toxoplasma. However, mutations within the organellar genomes of mitochondria and plastids can lead to drug resistance. Such mutations ultimately challenge our ability to control and eradicate the diseases caused by these pathogenic protists. Therefore, it is important to understand how organellar genomes, and the resistance mutations encoded within them, are inherited during protist sexual reproduction and how this may impact the spread of drug resistance and future therapeutic approaches to target these organelles. In this review, we detail what is known about mitochondrial and plastid inheritance during sexual reproduction across different pathogenic protists, often turning to their better studied, nonpathogenic relatives for insight.